Dobrostan dziecka, dobrostan rodziny i dobrostan dziecka w kontekście rodziny: przegląd i porównanie trzech koncepcji = Child Well-Being, Family Well-Being, and Child Well-Being in the Family Context: A Review and Comparative Analysis of Three Concepts - Nikel, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article reviews the definitions, theories, and research on three related yet distinct concepts: child well-being, family well-being, and child well-being in the context of the family. Child well-being includes both objective conditions (health, education, financial situation) and experiences (happiness, social relationships). Family well-being concerns the functioning of the whole family system, encompassing relationship quality, financial stability, health, and coping capacity. Child well-being in the context of the family integrates these perspectives, focusing on how family factors-such as security, emotional support, shared activities, and material resources-shape a child`s development.
Keywords: dobrostan dziecka; dobrostan rodziny; dobrostan dziecka w kontekście rodziny; dziecko; rodzina; child well-being; family well-being; child well-being in the context of the family; child; family